Pembuatan Disinfektan sebagai Upaya Pemeliharaan Lingkungan Pasca Pandemi - Handini Novita Sari; Parama Diptya Widayaka; Anggi Rahmad Zulfikar; Ronggo Alit; Bonda Sisephaputra (LPPM Universitas Bumigora, 2022)
Covid 19 cases that have begun to decline to the government's policy of loosening the wearing of masks in open spaces, do not mean that Covid 19 has disappeared from Indonesia. A healthy environment is something we still need to maintain in this post-Covid 19 pandemic era. The partner in this activity, namely the An-Nur Mushola Management, needs education about the sterilization of places of worship because the location is right on the edge of the highway which is crowded with activities coupled with the location of the Mushola which is adjacent to the kindergarten (Kindergarten) and elementary school (elementary school) this is clearly related to the health and safety of the pilgrims and also the students in the environment. Currently, the management of the Place of Worship really hopes for assistance in the form of health protocol facilities and education on the implementation of sterilization. Based on the explanation from the partner, the main needs during this pandemic are knowledge about the manufacture of disinfectant liquids, how to implement health protocols, and the disinfection process of the place. Based on the problems faced by the partners, researchers through community service activities entitled